Pilihan tipe co-management konservasi hutan rawa mangrove dalam kasus kehadiran kelompok peduli pesisir - Septia Wulandari Tia; Wanti Fitrianti (Holistic: Journal of Tropical Agriculture Sciences, 2023)
It is not yet known whether the success of mangrove swamp forest conserva-tion in Setapuk Besar was driven more by the participation of members of the coastal care group or by involving non-members. It is important to analyse this problem, in order to determine the option co-management types, after the mangrove forest rehabilitation activities is deemed successful. This study aims to analyze the implications of the presence of coastal care groups and community participation on the option types of co-management mangrove forest conservation. The research method uses a quantitative and qualitative approach. Quantitative data were collected through structured interviews with 90 respondents, while the analytical tools used descriptive methods and the difference test of Mann Whitney-U. The results of the study show that the level of understanding and participation of group members has significantly higher qualifications than non-members, so this indicates that there is still a high gap. This difference in understanding and participation is shown in the high ability of group members to analyze, interpret, understand environmental conditions, as well as their concern for consevation activities. The success of conservation which still relies on the participation of group members needs to be continuously improved by improving its management capacity, so that the level of participation can be higher by involving most members of the community. In this regard, considering that there is a real role for the coastal care group but there are gap of understanding and participation, the option about co-management form that considered appropriate is cooperative type.